The Relationship Between Self-Concept and Direction of Student Career Maturity at SMK Negeri 6 Padang - Intan Desy Pratiwi; Netrawati Netrawati (Jurnal Neo Konseling, 2021)
Vocational High School (SMK) is a means of education to prepare students to be ready to enter the world of work. Students must have good career maturity, their career choices should be mature, in the sense that in adolescence the individual is able to plan, think about, and choose a career for himself by making an effort to identify himself, find out about work and educational steps and overcome problems related to career selection. This research is motivated by the existence of several students who have not been able to plan their future careers and there are some students who have the belief that success is determined by luck, opportunity and fate. The objectives of this study were (1) to describe the self-concept, (2) to describe the direction of student career maturity in school and (3) to examine the relationship between self-concept and the direction of student career maturity at State Vocational High School 6 Padang. This type of research uses a quantitative approach with a correlational description method, with a sample of 187 students of SMK Negeri 6 Padang, using simple random sampling technique. The instrument used in this study was a questionnaire distributed through the Google Froms application. Based on the Likert scale. Data were analyzed using descriptive statistical techniques and Pearson Product Moment correlation techniques with the help of the SPSS program. The results revealed that: (1) Self-concept was in the medium category with a frequency of 51.34%, (2) the direction of career maturity of students at school tended to be in the fairly mature category with a frequency of 47.59%, and (3) There was a significant positive relationship between self-concept. with the direction of student career maturity with a correlation coefficient of 0.967 and a significance level of 0.000. Based on these findings, it is hoped that the counselor will always improve and develop guidance and counseling services, especially career guidance services to help students improve their career maturity.